KHOIRU UMMAH DAN TANGGUNG JAWAB SOSIAL (UNSUR MPM DAN LAZISMU) - Ikbal Nur Ghaffar (Universitas Muhammadiyah Surakarta, 2022)
The purpose of this study is to discuss the role of MPM (Majelis Pendidikan Dasar dan Menengah (Majelis Pendidikan Primer dan Menengah Tum) and Lazismu (Lembaga Amil Zakat, Infaq, and Sedekah Muhammadiyah) in creating Khoiru Ummah as well as better social responsibility through education and social welfare. This study briefly discusses the understanding of Khoiru Ummah Muhammadiyah, the role of MPM in creating a good and quality educational environment, and the role of Lazismu in managing zakat, infaq, and alms to improve the social welfare of the community. The result of this research is that MPM and Lazismu have an important role in creating Khoiru Ummah and social responsibility by contributing to the field of education and social welfare. In this study, several suggestions were also explained for MPM and Lazismu in improving service quality, synergy with other institutions, developing innovative and effective programs, and optimizing the use of information technology. It is hoped that by carrying out these suggestions, MPM and Lazismu can continue to contribute in creating a better Khoiru Ummah Muhammadiyah and provide greater benefits to the community.